2012
DOI: 10.1074/mcp.m111.014258
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of the Chromatin Proteome in Disease Reveals Remodeling Principles and Identifies High Mobility Group Protein B2 as a Regulator of Hypertrophic Growth

Abstract: A fundamental question in biology is how genome-wide changes in gene expression are enacted in response to a finite stimulus. Recent studies have mapped changes in nucleosome localization, determined the binding preferences for individual transcription factors, and shown that the genome adopts a nonrandom structure in vivo. What remains unclear is how global changes in the proteins bound to DNA alter chromatin structure and gene expression. We have addressed this question in the mouse heart, a system in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
75
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 51 publications
3
75
0
Order By: Relevance
“…They suggest general principles for global shifts in chromatin accessibility: altered linker to core histone ratio; differing abundance of chromatin structural proteins; and reprogrammed histone post-translational modifications. 37 Finally, like HMGB1, HMGB2 might be involved in regulation of telomerase activity and lead to telomere dysfunction. Knockout of the HMGB1 gene in mouse embryonic fibroblasts results in chromosomal abnormalities, enhanced colocalization of γH2AX foci at telomeres and a moderate shortening of telomere lengths.…”
Section: Discussionmentioning
confidence: 99%
“…They suggest general principles for global shifts in chromatin accessibility: altered linker to core histone ratio; differing abundance of chromatin structural proteins; and reprogrammed histone post-translational modifications. 37 Finally, like HMGB1, HMGB2 might be involved in regulation of telomerase activity and lead to telomere dysfunction. Knockout of the HMGB1 gene in mouse embryonic fibroblasts results in chromosomal abnormalities, enhanced colocalization of γH2AX foci at telomeres and a moderate shortening of telomere lengths.…”
Section: Discussionmentioning
confidence: 99%
“…Different cell types ought to have different chromatin structure underpinning their different transcriptomes, although most of the knowledge on endogenous chromatin structure (4,14,15) and the non-nucleosome proteins that regulate it (16,17) comes from non-cardiac cells, with some exceptions (18). At the level of the whole nucleus, we have reported a decrease in trimethylation of lysine 9 on histone H3 (H3K9me3), 8 a marker of constitutively silenced DNA (19), and an increase in H3K4me3 abundance, a marker of active expression (20), in failing hearts after transverse aortic constriction (21). Similarly, decreased H3K9me2 and increased H3K4me2 in the heart were observed in a mouse model of diabetes with glomerulosclerosis, a condition that can lead to heart disease in humans and induces hypertrophy of the cardiomyocytes in mice (22).…”
mentioning
confidence: 99%
“…Gene Expression-We previously found that hmgb2-regulated genes are enriched in pathways important to cardiac hypertrophy (21). We next asked how Hmgb2 and Ctcf regulate mRNA expression to explain why some hmgb2-regulated genes are up-regulated and others are down-regulated in response to hmgb2 knockdown in cardiomyocytes (21).…”
Section: Interaction Of Ctcf and Hmgb2 With Local Chromatin Features mentioning
confidence: 99%
See 2 more Smart Citations